The effective key drivers on regional innovation in Iranian metropolises with a future research approach (case study: Tabriz metropolis) - ameneh alibakhshi; mohammadreza pourmohammadi; rasoul ghorbani (تحقیقات کاربردی علوم جغرافیایی)
In recent decades, one of the main challenges in studies related to regional development is the search for understanding the economic and cultural differences between the national and regional levels in order to predict the transition that will lead to regional development. One of the systems that plays an important role in regional development is the regional innovation system. To this end, the aim of the present study is to identify the key drivers of regional innovation in the Tabriz metropolis. In this regard, the study is applied in terms of purpose and descriptive-analytical in nature. Two library and field methods were used to collect the required information. The statistical population of the study includes 32 qualified individuals in the industry, university, and government sectors who were selected as purposive sampling. The data were also collected from the Miqmac software for analysis. The research findings show that out of a total of 71 influential factors, 13 factors include an appropriate productivity culture, laws and regulations, the existence of a teamwork culture between activists and established industry units, information and communication technology infrastructure, sufficient funding for university research infrastructure, higher education, patent programs, higher education policy, performance evaluation and payment system, financial support, a special and flexible tax system for research and development, and research centers.